(untitled) (Bangladesh Journal of Animal Science, 2014)
This experiment was conducted to determine and compare some characteristics of the meat and carcass of rabbit aged 6 months according to sex. In the experiment six male and six female nondescript rabbits were slaughtered. The weight and percentage of warm carcasses, skin with head and limbs, liver, kidney, heart, lung, forelegs, hind legs, breast and ribs, loin and abdominal wall were recorded. The values for carcass length, lumbar circumference, drip loss, cooking loss, sensory characteristics were also determined. The mean values for warm carcass weight and warm dressing percentage were 698.33g and 47.92% in male and 704.66g and 48.55% in female, respectively. In case meat quality cooking loss, drip loss, proximate and sensory analyses was conducted. In this study significance difference was found in head, skin and limb weight (93.34 g) as well as in percentage (6.46%) otherwise no significant differences were found between male and female rabbits in the characteristics of carcass and meat quality. Slaughter weight was significantly correlated with the weights of carcass, skin with head and limbs, lung, liver, kidney, heart and weight of joints and dressing percentage. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20718 Bang. J. Anim. Sci. 2014. 43 (2): 154-158